High-density lipoprotein cholesterol: How High - Rajagopal, G. (Medknow Publications & Media Pvt Ltd, 2012)
The high-density lipoprotein cholesterol (HDL-C) is considered anti-atherogenic good cholesterol. It is involved in reverse transport of lipids. Epidemiological studies have found inverse relationship of HDL-C and coronary heart disease (CHD) risk. When grouped according to HDL-C, subjects having HDL-C more than 60 mg/dL had lesser risk of CHD than those having HDL-C of 40-60 mg/dL, who in turn had lesser risk than those who had HDL-C less than 40 mg/dL. No upper limit for beneficial effect of HDL-C on CHD risk has been identified. The goals of treating patients with low HDL-C have not been firmly established. Though many drugs are known to improve HDL-C concentration, statins are proven to improve CHD risk and mortality. Cholesteryl ester transfer protein (CETP) is involved in metabolism of HDL-C and its inhibitors are actively being screened for clinical utility. However, final answer is still awaited on CETP-inhibitors.